ARABIC LANGUAGE LEARNING THROUGH THE CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) APPROACH TO DEVELOP LANGUAGE SKILLS AT MA’HAD HIDAYATULLAH BATU. - Haikal Ibrahim, Fikri; Wargadinata, Wildana; Hasan, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the implementation of Arabic language learning through the Content and Language Integrated Learning (CLIL) approach at Hidayatullah Islamic Boarding School Batu, identify its supporting and inhibiting factors, and examine its impact on students’ language skills development. This research employed a qualitative descriptive-analytical approach. Data were collected through observation, interviews, and documentation involving the head of the boarding school, the principal, Arabic language teachers, and students. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing, while triangulation was used to ensure data validity. The findings revealed that the implementation of the CLIL approach integrated the four main components of CLIL: Content, Communication, Cognition, and Culture. Arabic was used as the medium for learning Islamic and cultural content through discussions, dialogues, text analysis, and interactive activities. Supporting factors included institutional support, teacher competence, a conducive language environment, and students’ learning motivation. Inhibiting factors included differences in students’ language proficiency, limited use of Arabic outside the classroom, and inadequate learning media. The study also found that the CLIL approach positively contributed to the development of students’ listening, speaking, reading, and writing skills, as well as improving their linguistic and communicative competence in Arabic. Therefore, the study concludes that the CLIL approach is effective in enhancing students’ Arabic language skills and communicative competence at Ma’had Hidayatullah Batu.